PEMODELAN DAN SIMULASI SISTEM PEMBANGKIT TURBIN GAS PLTGU TANJUNG PRIOK - Indrawanto, Indrawanto; Cahyono, H (Mesin, 2009)
This paper presents the modeling and simulation of the gas turbine generating system of Tanjung Priok Combined Cycle Power Plant. The gas turbine model is approximated using steam turbine systems. The model developed only accepts load changes as input to the system. Three types of control systems; speed-droop governor, speed-droop governor with integral control, and speed-droop governor with integral and derivative control have been tried to control the frequency of the system. The simulation results show that, in the presence of load changes, the speed-droop governor with integral and derivative control is able to bring back the system frequency to 50 Hz without oscillation.